KINERJA APARAT KEPOLISIAN DALAM PELAYANAN ADMINISTRASI KEPEGAWAIAN PADA BAGIAN SUMBER DAYA MANUSIA KANTOR KEPOLISIAN RESOR MOROWALI UTARA - Yulius Batulapa; Juemi Juemi; Ince Dian Afnita (Program Studi Magister Ilmu Manajemen Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2025)
his study aims to analyze the performance of police officers in administrative personnel services at the Human Resources Division of the North Morowali Police Resort. This research employs a qualitative method with a descriptive approach, selecting informants through purposive sampling. Data were collected through observation, interviews, and documentation. The findings indicate that productivity, responsibility, and accountability in administrative personnel services have been well implemented. Police officers are capable of operating technology-based administrative systems such as the SiSDM application to support work efficiency. However, service quality and responsiveness still face challenges, including limited personnel, unstable network access to the system, and a lack of continuous training. Overall, while administrative personnel services have been functioning adequately, improvements in technological infrastructure and human resource development are necessary to enhance service effectiveness and quality.